ANALISIS VARIASI JUMLAH BLADE PADA HORIZONTAL AXIS WIND TURBINE TIPE TAPERLESS AIRFOIL SG6043 MENGGUNAKAN METODE BEM DAN CFD - Pratama Ricky Novianto (2023)
The design of taperless type blades using Airfoil SG6043 with variations in the number of blades using BEM and CFD simulation methods is expected to be a reference in determining the design that produces the best work efficiency. The simulation results obtained the largest Cp value in the Taperless blade design is a blade design with variations in the number of 3 wind turbine blades which have a value of Cp = 0.45 in the BEM simulation and have a value of Cp = 0.364 in the CFD simulation. The largest Cp value in the Taperless blade design is a blade design with a variation in the number of 4 wind turbine blades which has a value of Cp = 0.48 in the BEM simulation and has a value of Cp = 0.425 in the CFD simulation. While the largest Cp value in the Taperless blade design is a blade design with a variation in the number of 5 wind turbine blades which has a value of Cp = 0.47 in the BEM simulation and has a value of Cp = 0.450 in the CFD simulation. There is a difference in the highest Cp values for BEM and CFD methods. To be a reference or more valid result, of course, with the CFD method because the BEM method can only be used to estimate the initial performance of wind turbines and then the design of wind turbines can be optimized with detailed observations using the CFD method.